Enhancing Lecturer Quality In The Digital Era: A Case Study Of Islamic Higher Education In East Java - Muhith, Abd; Hepni; Sulthoniyah, Luluk; Dewi, Rosita Fitrah; Ramadhan, Firman Aulia; Khalid, Zakariya Anshari Khalid bin; Ghani, Faizal Abdul; Sholeh, Muh Ibnu (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2025)
This study aims to explore strategies for accelerating the improvement of lecturer quality in the digital era at LPTNU Bondowoso, focusing on the role of digital competency training, continuous professional development, and institutional support in enhancing teaching effectiveness and research productivity in Islamic higher education. A qualitative research approach was employed, involving interviews, observations, and document analysis. Data were collected from lecturers at six institutions under LPTNU Bondowoso, including STAI At-Taqwa, STIS Abu Zairi, STAI Al Maliki, STIS Darul Falah, STAI Al Utsmani, and STIT Togo Ambarsari. The data were analyzed using thematic analysis, a systematic method for identifying and interpreting patterns within qualitative data. The process involved familiarizing with the data, generating initial codes, organizing them into themes, refining and defining those themes, and finally producing a coherent report. This approach allowed the researcher to explore key themes related to the use of digital technology in teaching and research, while capturing the diverse experiences of the lecturers. The study found that effective digital competency training, combined with ongoing professional development and strong institutional support, significantly enhances lecturers’ teaching effectiveness and research productivity. Key strategies identified include the use of digital tools for research, innovative teaching methods, and the ethical integration of technology in line with Islamic values. Additionally, structured workshops and mentorship programs were highlighted as essential for building digital literacy and academic writing skills. These findings provide valuable insights for educational leaders and policymakers in Islamic higher education institutions, emphasizing the need for a holistic approach that integrates technical training, ethical guidance, and administrative support to strengthen the digital competence of lecturers. Supporting materials include interview transcripts, observation notes, and institutional documents, providing comprehensive insights into the strategies for digital capacity building among lecturers at LPTNU Bondowoso